Preoperative peripheral blood inflammatory markers especially the fibrinogen-to-lymphocyte ratio and novel FLR-N score predict the prognosis of patients with early-stage resectable extrahepatic cholangiocarcinoma - Li, Shijie; Zhang, Xingli; Lou, Changjie; Gu, Yuanlong; Zhao, Juan (Frontiers in Oncology, 2022)
Background: Systemic inflammation is important in the development of extrahepatic cholangiocarcinoma (ECC). The aim of this study was to compare the prognostic power of preoperative peripheral blood inflammatory markers and the novel FLR-N score in patients with resectable ECC. Methods: A total of 140 patients with resectable ECC and 140 healthy controls (HCs) were recruited for the study. The Mann‒Whitney U test was used to evaluate the differences in inflammatory markers between groups. Kaplan‒Meier and Cox regression analyses were used to evaluate the prognostic power of preoperative fibrinogen, albumin, prealbumin, bilirubin, neutrophils, lymphocytes, monocytes, platelets, fibrinogen-to-lymphocyte ratio (FLR), fibrinogen-to-albumin ratio (FAR), fibrinogen-to-prealbumin ratio (FPR), neutrophil-to-lymphocyte ratio (NLR), platelet-to-lymphocyte ratio (PLR), monocyte-to-lymphocyte ratio (MLR), FLR-neutrophil (FLR-N) score, and CA19-9 in patients with resectable ECC. Nomogram was developed based on the results of multivariate Cox analyses. Results: Patients with resectable ECC had significantly higher levels of neutrophils, monocytes, fibrinogen, FLR, FAR, FPR, NLR, PLR, and MLR and lower levels of lymphocytes, albumin, and prealbumin than HCs (all P < 0.01). Albumin, prealbumin, and FPR had a good ability to distinguish between ECC patients with total bilirubin < 34 µmol/L and HCs (AUCs of 0.820, 0.827, and 0.836, respectively). Kaplan‒Meier analysis showed that high neutrophil, fibrinogen, FLR, FAR, PLR, MLR, and FLR-N score values were associated with poor survival in patients with resectable ECC. Multivariate analyses indicated that neutrophils (P = 0.022), FLR (P = 0.040), FLR-N score (P < 0.0001), and positive lymph node metastasis (P = 0.016) were independent factors for overall survival (OS). Nomogram were developed to predict OS for patients with ECC. Conclusion: The prognostic roles of inflammatory markers in patients with resectable ECC were different. The preoperative neutrophil count, FLR and FLR-N score could serve as noninvasive markers for predicting the prognosis of resectable ECC.